Perancangan Signage Dan Wayfinding di Pantai Nongsa Batam - Harahap, Widiya Lestari; Septiana, Reski; Nethania, Evelyn (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Nongsa Beach in Batam is an increasingly popular tourist destination, facing challenges in providing an effective signage and wayfinding system. The lack of a clear information system often causes confusion among visitors, especially for first-time visitors. This research aims to design signage and wayfinding systems that not only improve readability and understanding of information, but also enrich the visitor experience by creating a more organized and accessible environment. This study uses the environmental graphic design (EGD) method which is limited to predesign and design. Data collection was taken from observation, interviews and literature studies and analyzed. The results of the data analysis were used to design Signage and Wayfinding at Nongsa Beach, Batam.